2004
DOI: 10.1089/089771504323004575
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Human Spinal Cord Injury: Defining the Problems

Abstract: This article reviews the pathology of human spinal cord injury (SCI), focusing on potential differences between humans and experimental animals, as well as on aspects that may have mechanistic or therapeutic relevance. Importance is placed on astrocyte and microglial reactions. These cells carry out a myriad of functions and we review the evidence that supports their beneficial or detrimental effects. Likewise, vascular responses and the role of inflammation and demyelination in the mechanism of SCI are review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
433
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(454 citation statements)
references
References 43 publications
11
433
0
10
Order By: Relevance
“…19 The improvement in CMAP responses that we have observed in the current study might also be linked to the resolution of hemorrhage and edema in the spinal cord and/or ventral root, which is observed in the initial days following human SCI. 4 Restoration of the blood-brain barrier and extracellular ion and neurotransmitter homeostasis may also play important roles. However, in our rat cervical contusion model, we previously showed that CMAPs remain chronically reduced for at least 6 weeks, suggesting that these early events only account for partial CMAP loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The improvement in CMAP responses that we have observed in the current study might also be linked to the resolution of hemorrhage and edema in the spinal cord and/or ventral root, which is observed in the initial days following human SCI. 4 Restoration of the blood-brain barrier and extracellular ion and neurotransmitter homeostasis may also play important roles. However, in our rat cervical contusion model, we previously showed that CMAPs remain chronically reduced for at least 6 weeks, suggesting that these early events only account for partial CMAP loss.…”
Section: Discussionmentioning
confidence: 99%
“…1 We previously described a model of midcervical (C4) contusion in the adult rat. 2 We demonstrated that this paradigm models a number of the histopathological and functional features seen in human patients, 3,4 including extensive PhMN loss, phrenic nerve axonal degeneration, diaphragm atrophy, and chronically persistent unilateral diaphragm deficits, such as decreased diaphragm compound muscle action potential (CMAP) amplitudes following phrenic nerve stimulation, making it a clinically relevant model of respiratory compromise following midcervical contusion SCI. Nevertheless, experimental data are lacking regarding the timing of early PhMN loss and the consequent role of gray matter sparing on global breathing function during the initial stages following midcervical spinal contusion.…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the adult human cervical spinal cord dorsal columns leads to sensory dysfunctions of the upper limbs as evidenced by transient exaggeration or abolishment of the cutaneous sensations of fine touch, vibration, and proprioception (for a review, see York, 1985;Nathan et al, 1986). Similarly (Metz et al, 2000;Norenberg et al, 2004), transient and persistent upper limb cutaneous sensation dysfunctions occur in adult rats with damage to their cervical spinal cord dorsal columns (Schrimsher and Reier, 1993;McKenna and Whishaw, 1999;Ballerman et al, 2001a,b;Onifer et al, 2005;Kanagal and Muir, 2007). Abolished upper limb somatosensory evoked potentials (SSEPs) also can recover spontaneously in persons with incomplete cervical SCI (Curt and Dietz, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Staining of sections taken from areas considered positive for schwannosis in PPD-stained plastic sections were negative for the presence of Schwann cells. We speculate that instead these structures are primarily composed of fibroblasts (i.e., mesenchymal-derived), similar to the mesenchymal scar described in human spinal cord injury patients, primarily after a laceratingtype of injury (Berry et al, 1983;Norenberg et al, 2004).…”
Section: Figmentioning
confidence: 66%
“…The presence of hypertrophic astrocytes, but the lack of astrocytic scar formation, in minipigs is similar if not identical to what has been described in human spinal cord specimens taken from patients at chronic stages of spinal cord injury. In these studies the presence of hypertrophic astrocytes was described; however, no typical astrocyte scar was identified (Norenberg et al, 2004). These authors' characterization included ''.…”
Section: Figmentioning
confidence: 99%